Cytological patterns of cervical pap smears with histopathological correlation - Atla, Bhagya Lakshmi; Uma, Prasad; Shamili, M.; Kumar, S. Satish (International Journal of Research in Medical Sciences, 2017)
Background: Cervical cancer is the most common, preventable cancer and does not develop suddenly from normal epithelium but is presented by a spectrum of intraepithelial neoplasia. Pap smear is an ideal screening and low cost effective test to detect intraepithelial neoplasia especially in developing countries but has limitations and needs confirmation by histopathology. The study aimed to determine the sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of pap smears as screening test in cervical lesions by comparing with histopathology. Methods: This is a prospective study conducted at a tertiary care centre in Department of pathology from October 2012 to September 2014. A complete clinical history and demographic status of the subjects was recorded. Conventional pap smears were reported adopting Bethesda system and biopsies were taken in cases of epithelial cell abnormality, routinely processed and stained with H&E. Results: Total number of pap smears analysed were 356. NILM (negative for intraepithelial lesions or malignancy) constituted major group 248/356 (69.64%) and epithelial cell abnormality were 98/356 (27.5%). In the present study overall sensitivity was 94.11% specificity 64.28% positive predictive value 82.75%,negative predictive value 85%,diagnostic accuracy 83.33%,concordance rate 78.2% and P value <0.001. Concordance rate for CIN I was 78.9%, for CINII and CINIII 60% and for squamous cell carcinoma 100%. Conclusion: Pap smear is simple, inexpensive and can be performed in the outpatient department. Hence, it should be recommended routinely as a method of improving reproductive health, early detection of premalignant and malignant cervical lesions.